2013
DOI: 10.1007/s12262-013-1002-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Laparoscopic Distal Pancreatectomy with or without Splenic Preservation

Abstract: Laparoscopic distal pancreatectomy (LDP) has gained large popularity in recent years, although the choice of whether to preserve the spleen has remained inconsistent. The aim of our study was to report our experiences with LDP and to provide evidence for the safety of the operative technique and an evaluation index of splenic function. We retrospectively evaluated all LDPs performed at our institution between March 2008 and February 2012. Cases were divided into a laparoscopic spleen-preserving distal pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The search strategy yielded 411 articles and we checked the title and abstract of the studies according to the inclusion and exclusion criteria and selected 53 articles. After the full texts of the remaining articles were read, 15 articles were included in the meta-analysis of MI-SPDP versus MI-DPS [13,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] and 15 articles were included in the meta-analysis of MI-SVP versus MI-WT [13,23,[31][32][33][34][35][36][37][38][39][40][41][42][43]. Figure 1 shows the flow diagram of study identification and evaluation during the review process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search strategy yielded 411 articles and we checked the title and abstract of the studies according to the inclusion and exclusion criteria and selected 53 articles. After the full texts of the remaining articles were read, 15 articles were included in the meta-analysis of MI-SPDP versus MI-DPS [13,[17][18][19][20][21][22][23][24][25][26][27][28][29][30] and 15 articles were included in the meta-analysis of MI-SVP versus MI-WT [13,23,[31][32][33][34][35][36][37][38][39][40][41][42][43]. Figure 1 shows the flow diagram of study identification and evaluation during the review process.…”
Section: Resultsmentioning
confidence: 99%
“…In the LWT group, 48 (24.9%) of 193 patients showed splenic infarction (symptomatic or asymptomatic). Meta-analysis showed the ratio of splenic infarction was [13,19,20,22,29] significantly lower in the LSVP group compared with in the LWT group (OR 0.14; 95% CI: 0.08, 0.26), and there was no heterogeneity between the trials (P = 0.97;…”
Section: Subanalysis Between Laparoscopic Splenic Vessel Preservationmentioning
confidence: 97%
“…Nowadays, laparoscopic distal pancreatectomy has become the preferred approach, especially for benign and low-grade malignant lesions [12] [13]. There are a limited number of studies comparing laparoscopic spleen-preserving distal pancreatectomy (LSPDP) with laparoscopic distal pancreatectomy with splenectomy (LDPS) and the reported results on postoperative morbidity are inconsistent [14][15][16][17][18]. Moreover, outcomes are likely to be impacted by treatment allocation bias due to the retrospective nature of the studies and the conversion from LSPDP to LDPS due to intraoperative events.…”
mentioning
confidence: 99%
“…Spleen preserving distal pancreatectomy is the preferred procedure for benign or borderline pancreas body and tail mass because of the important role of the spleen in maintaining immunological function and in reducing the risk of cancer [615]. Previous studies showed that splenic vessel-sacrificing distal pancreatectomy had a significant risk for splenic infarction and left-sided portal hypertension including gastric varices compared to splenic vessel-preserving distal pancreatectomy [81112].…”
Section: Discussionmentioning
confidence: 99%